Long survival of patients with metastatic clear cell renal cell carcinoma. Results of real life study of 344 patients. Issue 6 (1st August 2019) - Voog, Eric; Campillo‐Gimenez, Boris; Elkouri, Claude; Priou, Franck; Rolland, Frederic; Laguerre, Brigitte; Elhannani, Chaza; Merrer, Jacques; Pfister, Christian; Sevin, Emmanuel; L'Haridon, Tifenn; Hasbini, Ali; et al.
Abstract : The treatment landscape in metastatic renal cell carcinoma has changed fundamentally over the last decade by the development of antiangiogenic agents, mammalian target of rapamycin inhibitors and immunotherapy. Outside of the context of a clinical trial, the treatments are used sequentially. We describe results under real‐life conditions of a sequential treatment strategy, before the era of immunotherapy. All patients were treated according to their prognostic score (either Memorial Sloan Kettering Cancer Center or International Metastatic Renal Cell Carcinoma Database Consortium) for advanced renal cell carcinoma. A treatment strategy involving 1 to 4 lines was determined including a rechallenge criterion for the repeat use of a treatment class. Three hundred forty‐four patients were included over 3 years. Overall survival was 57 months in patients with good or intermediate prognosis and 19 months in patients with poor prognosis. In the former group, the proportions of patients treated with 2 to 4 treatment lines were 70%, 38% and 16%, respectively. The best objective response rates for lines 1 to 4 were 46%, 36%, 16% and 17%, respectively. Grade III/IV toxicity did not appear to be cumulative. The recommended strategy was followed in 68% of patients. A large proportion of patients with good or intermediate prognosis who progress after two lines of treatment still have a performance status good enough to receive a systemic treatment, which justifies such a strategy. Overall survival of patients with good and intermediate prognosis was long, suggesting a benefit from the applied approach. These results might be used as selection criterion for the treatment of patients in the era of immune checkpoint inhibitors. Abstract : What's new? Metastatic renal cancer is a notoriously relapsing disease that can be treated with anti‐angiogenic treatments, tyrosine kinase inhibitors, inhibitors of the mammalian Target of Rapamycin or immune checkpoint inhibitors. The authors performed a "real‐life" study testing a sequential strategy of the first three treatments applied to 344 patients with relapsing metastatic renal cancer before the era of immunotherapy. They found that the overall survival of patients with good and intermediate prognosis was long, almost 5 years, and plan a new study including immunotherapy in the future.